Industrial IoT Edge Computing Platform for Real-Time Monitoring - Sorayut Glomglome; Watanyou Damrongphokaphan; Kittisak Phormraksa; Korntawat Witchuvanit (My University, 2022)
This research’s goal is to develop an industrial IoT edge computing platform for Industrial IoT 4.0 that are currently in the process of transitioning from legacy systems to adopting IoT system. Due to connecting and collecting data from each machine part is still a problem of transition from the old system, this is the origin of this research. The system consists of a Remote Terminal Unit (RTU) which collect data from machines with sensors and an Edge Computing Device used to collect data from RTUs via MQTT Protocol. The system also has an IoT platform that processes incoming data for storing in the database and displays on the Web Application in real time and in retrospect and can also alert to Line Notify according to the conditions predefined by the user. Based on the benchmark test, an edge computing device can concurrently handle RTU connections up to 800 connections.
Keywords: IoT and Edge/Fog Computing; Cloud Computing and Resource Management; Data Stream Mining Techniques